A three-dimensional layered porous carbon nanotube foam and preparation method thereof
By using a mixed solution of hydrochloric acid and hydrogen peroxide to promote rapid expansion of carbon nanotube films, the problems of long expansion time and insufficient foam thickness in the prior art were solved, and three-dimensional layered porous carbon nanotube foam with low density and diverse structures were prepared to meet the needs of many aspects.
Patent Information
- Application Number
- CN202211460092.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-11-17
AI Technical Summary
In the preparation of three-dimensional carbon nanotube foam, the existing technology has problems such as long expansion time and relatively thin foam thickness after expansion, which cannot meet the needs of many aspects.
A mixed solution of hydrochloric acid and hydrogen peroxide is used as the oxidation solution, and the carbon nanotube film is soaked in the solution. The large number of bubbles generated are used to achieve rapid expansion of the carbon nanotube film. Then neutralize with sodium hydroxide solution and rinse with deionized water to remove impurities, and finally obtain a three-dimensional layered porous carbon nanotube foam by drying.
It has achieved rapid preparation of carbon nanotube foam with a density as low as ~1.0g/cm3, a pore structure with high specific surface area and multi-stage layering, and is suitable for energy storage, oil adsorption, electromagnetic shielding and other fields.
Smart Images

Figure CN115744883B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a three-dimensional layered porous carbon nanotube foam and a preparation method thereof. Background Art
[0002] Carbon nanotubes are one of the allotropes of carbon and have excellent mechanical, electrical and thermal properties. For most practical applications, macroscopic materials are required, so it is necessary to assemble individual carbon nanotubes into macroscopic components while maintaining their excellent properties. After more than ten years of research, multi-dimensional components based on carbon nanotubes have been prepared, such as one-dimensional carbon nanotube fibers, two-dimensional carbon nanotube films, and three-dimensional carbon nanotube foams. Among all these structures, three-dimensional carbon nanotube foams have attracted more and more attention due to their high specific surface area, multi-level hierarchical pore structure, well-connected conductive network, strong electron transport ability, and a large number of active sites, which can meet different application requirements.
[0003] The preparation of carbon nanotube foam usually adopts the sol-gel method and chemical vapor deposition method. The sol-gel method is to disperse carbon nanotubes in an aqueous solution, form a dense three-dimensional hydrogel structure under the bonding effect of the gel material, and then remove the water by freeze drying or critical drying to finally obtain a foam structure. The disadvantage of this method is that the length and mass of carbon nanotubes are limited, and the covalent bonds between carbon nanotubes are weak. Therefore, the electrical and mechanical properties of carbon nanotube foam prepared by the sol-gel method are limited and it is usually fragile.
[0004] Compared with the multi-step and time-consuming sol-gel method, chemical vapor deposition is an efficient and rapid one-step synthesis method that can prepare carbon nanotube foams with a certain orientation while maintaining excellent mechanical and electrical properties. However, based on the nature of the chemical vapor deposition method, it is still very difficult to in situ control the type of carbon nanotubes (the number and chirality of carbon nanotube walls) and the shape of the foam, and it is also difficult to remove residual catalysts under mild conditions during the growth of carbon nanotube foams.
[0005] For the above problems of sol-gel method and chemical vapor deposition method, US Patent US 9102537 B2 discloses an innovative method for preparing three-dimensional ultralight pure carbon nanotube foam, which is to place the carbon nanotube film in a mixed solution of sulfuric acid and hydrogen peroxide at room temperature for spontaneous expansion, and then freeze-dry to obtain carbon nanotube foam. Luo et al. (Self-Expansion Construction of Ultralight Carbon Nanotube Aerogels with a 3Dand Hierarchical Cellular Structure, small 2017, 13, 1700966.) reported the use of the same method to prepare carbon nanotube foam, using this method, the carbon nanotube film was immersed in an oxidizing solution for 24 hours and the thickness reached only 0.35cm.
[0006] However, the method of obtaining three-dimensional ultra-light pure carbon nanotube foam by spontaneously expanding carbon nanotube film in a mixed solution of sulfuric acid and hydrogen peroxide at room temperature has the defects of long expansion time and relatively thin thickness of the expanded nanotube foam, which cannot meet the various applications of nanotube foam. Summary of the invention
[0007] In order to solve the above problems existing in the prior art, the present invention provides a three-dimensional layered carbon nanotube foam and a preparation method thereof. The preparation method is as follows: a mixed solution of hydrochloric acid and hydrogen peroxide is used as an oxidizing solution, a carbon nanotube film is immersed in the oxidizing solution, a large number of bubbles generated in this process are used to expand the carbon nanotube film, and then a sodium hydroxide solution is used to neutralize it until the pH is 7, and then it is further rinsed with deionized water to remove the remaining impurities, and finally the carbon nanotube foam is obtained by drying.
[0008] Because the reaction of hydrochloric acid and hydrogen peroxide releases a large amount of hydrogen and oxygen, the carbon nanotube film structure immersed in the mixed solution of hydrochloric acid and hydrogen peroxide will continuously produce gas, causing the carbon nanotube film to expand to a certain height in just a few minutes. In this process, different containers can be selected to control the shape of the final carbon nanotube foam.
[0009] In order to achieve the above effects, the present invention adopts the following technical solutions:
[0010] The present invention provides a method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps of which are as follows:
[0011] 1) Shearing the carbon nanotube film;
[0012] 2) stirring the hydrogen peroxide solution and the hydrochloric acid solution to obtain an oxidation solution;
[0013] 3) placing the carbon nanotube film cut in step 1) in the oxidizing solution in step 2) to perform a self-expansion process of the carbon nanotube film;
[0014] 4) taking out the sample obtained in step 3), putting it into water, adding alkaline solution to neutralize it until the pH is 7, and washing impurities with water;
[0015] 5) Drying the sample obtained in step 4) to remove moisture, thereby obtaining a three-dimensional layered porous carbon nanotube foam.
[0016] Furthermore, the concentration of the hydrogen peroxide solution in step (2) is 30 wt %, and the concentration of the hydrochloric acid solution is 37 wt %.
[0017] Furthermore, in step (2), the volume ratio of hydrogen peroxide to hydrochloric acid is 1-3:1-3.
[0018] Furthermore, the self-expansion time in step (2) is 2 min to 4 min.
[0019] Furthermore, the self-expansion height in step (2) is 12 mm to 9 cm.
[0020] Furthermore, the self-expansion process in step (3) is carried out at room temperature or at 50°C to 70°C.
[0021] Furthermore, the concentration of the sodium hydroxide solution in step (4) is 0.5 mol / L to 4 mol / L.
[0022] Furthermore, the drying method in step (5) is any one of the following: room temperature drying, vacuum drying, and freeze-drying.
[0023] Furthermore, in step (5), room temperature drying is drying at 25°C for 24 hours; vacuum drying is drying at 120°C for 1 hour; and freeze drying is freeze drying at -56°C for 18 hours.
[0024] Room temperature in the present invention refers to 25°C.
[0025] The preparation method of the invention is simple to operate and has a short reaction time, and can use the carbon nanotube film to manufacture ultra-light three-dimensional layered porous carbon nanotube foam with controllable density, structure and geometric shape.
[0026] Beneficial effects:
[0027] 1. Carbon nanotube foam has no restrictions on shape, size and pattern and can be used for large-scale production applications.
[0028] 2. The self-expansion time of carbon nanotube film is shortened from more than ten hours to a few minutes, the reaction time is short, the preparation process is simple and efficient.
[0029] 3. The prepared carbon nanotube foam has a high specific surface area, a multi-level pore structure, a well-connected conductive network, and a density as low as ~1.0g / cm 3 , can be widely used in energy storage, oil adsorption, electromagnetic shielding and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flow chart for the preparation of carbon nanotube foam.
[0031] Figure 2 This is a scanning electron microscope image of a carbon nanotube film.
[0032] Figure 3 It is a line graph showing the thickness of the carbon nanotubes changing with time during the self-expansion process in Example 1.
[0033] Figure 4 It is a comparison chart of the density, thickness, volume, width and length of the carbon nanotube film and the carbon nanotube foam of Example 1.
[0034] Figure 5 This is a sample picture of the carbon nanotube film after self-expansion in Example 4.
[0035] Figure 6 This is a physical picture of the carbon nanotube film and carbon nanotube foam of Example 7.
[0036] Figure 7 These are scanning electron microscope images of the carbon nanotube foam of Example 7 at different magnifications.
[0037] Figure 8 These are actual pictures of carbon nanotube foams of different shapes and patterns prepared in Example 3. From left to right in Figure A, the shapes of the carbon nanotube foams are rectangular (width greater than length), rectangular with a hole in the middle, rectangular (length greater than width), cylinder, and irregular body; Figure B is an enlarged actual picture of a part of the rectangular (length greater than width) carbon nanotube foam. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these embodiments. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application. The present invention is further described below in conjunction with embodiments and experimental results.
[0039] The carbon nanotube film used in the present invention has a scanning electron microscope image as shown in FIG. Figure 2As shown, the carbon nanotube film is composed of randomly arranged carbon nanotubes, and adjacent carbon nanotubes are tightly bound together by van der Waals forces to form an independent carbon nanotube film that does not require substrate support. In the present invention, hydrogen peroxide and hydrochloric acid are both commercially available products; the type and source of the carbon nanotube film are not limited, and it can be prepared using commercially available products known to those skilled in the art or according to a method for preparing a carbon nanotube film known to those skilled in the art.
[0040] Example 1
[0041] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0042] 1) Cut the carbon nanotube film (64 mm × 32 mm × 0.2 mm) into a shape with a hole pattern in the middle;
[0043] 2) Measure 40 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 40 mL of 37% hydrochloric acid solution and slowly pour it into the container containing the hydrogen peroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0044] 3) The cut carbon nanotube film is placed in an oxidizing solution to allow the carbon nanotube film to self-expand at room temperature; the expansion time is about three minutes and the height can reach 16 mm.
[0045] 4) Take out the expanded sample and place it in a beaker filled with water, add a 0.5 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it again with deionized water to remove impurities;
[0046] 5) Finally, the sample was placed in a vacuum oven and dried at 120° C. for 1 hour to obtain a three-dimensional layered porous carbon nanotube foam.
[0047] The line graph of the thickness of the carbon nanotubes during the self-expansion process of this embodiment changing with time is shown in FIG. Figure 3 As shown; the comparison of the density, thickness, volume, width and length of carbon nanotube film and carbon nanotube foam is shown in Figure 4 shown.
[0048] Example 2
[0049] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0050] 1) Cut the carbon nanotube film (64 mm × 32 mm × 0.2 mm) into a shape with a hole pattern in the middle;
[0051] 2) Measure 40 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 40 mL of 37% hydrochloric acid solution and slowly pour it into the beaker containing the hydrogen peroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0052] 3) The cut carbon nanotube film is placed in an oxidizing solution to allow the carbon nanotube film to self-expand at room temperature; the expansion time is about four minutes and the height can reach 25 mm.
[0053] 4) Take out the expanded sample and place it in a beaker filled with water, add 1 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it with deionized water again to remove impurities.
[0054] 5) Finally, the sample is placed at room temperature for drying for 24 hours to obtain a three-dimensional hierarchical porous carbon nanotube foam.
[0055] Example 3
[0056] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0057] 1) Cut the carbon nanotube film (64 mm × 32 mm × 0.2 mm) into a shape with a hole pattern in the middle;
[0058] 2) Measure 40 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 40 mL of 37% hydrochloric acid solution and slowly pour it into the beaker containing the hydrogen peroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0059] 3) The cut carbon nanotube film is placed in an oxidizing solution to allow the carbon nanotube film to self-expand at room temperature; the expansion time is about four minutes and the height can reach 23 mm.
[0060] 4) Take out the expanded sample and place it in a beaker filled with water, add a 2 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it again with deionized water to remove impurities;
[0061] 5) Finally, the sample was placed in a freeze dryer and freeze-dried at -56°C for 18 hours to obtain a three-dimensional layered porous carbon nanotube foam.
[0062] The present invention adopts the method described in Example 3 to prepare carbon nanotube foam, and designs the pattern of the carbon nanotube film in different ways. The prepared carbon nanotube foam sample is as follows: Figure 8 shown.
[0063] Example 4
[0064] 1) Cutting the carbon nanotube film into film slices of 110 mm × 80 mm × 0.165 mm;
[0065] 2) Measure 40 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 40 mL of 37% hydrochloric acid solution and slowly pour it into the beaker containing the hydrogen peroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0066] 3) The cut carbon nanotube film is placed in an oxidizing solution and the carbon nanotube film is subjected to a self-expansion process at room temperature. The expansion time is about four minutes and the expansion height reaches 9 cm.
[0067] 4) Take out the expanded sample and place it in a beaker filled with water, add a 3 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it again with deionized water to remove impurities;
[0068] 5) Finally, the sample was placed in a freeze dryer and freeze-dried at -56°C for 18 hours to obtain a three-dimensional layered porous carbon nanotube foam.
[0069] The sample of the carbon nanotube film after self-expansion in this embodiment is shown in FIG. Figure 5 shown.
[0070] Example 5
[0071] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0072] 1) Cutting the carbon nanotube film into film slices of 110 mm × 80 mm × 0.165 mm;
[0073] 2) Measure 30 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 60 mL of 37% hydrochloric acid solution and slowly pour it into the beaker containing the hydrogen peroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0074] 3) The cut carbon nanotube film is placed in an oxidizing solution to undergo a self-expansion process at room temperature. The expansion time is about four minutes and the expansion height reaches 30 mm.
[0075] 4) Take out the expanded sample and place it in a beaker filled with water, add a 3 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it again with deionized water to remove impurities;
[0076] 5) Finally, the sample was placed in a freeze dryer and freeze-dried at -56°C for 18 hours to obtain a three-dimensional layered porous carbon nanotube foam.
[0077] Example 6
[0078] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0079] 1) Cutting the carbon nanotube film into film slices of 110 mm × 80 mm × 0.165 mm;
[0080] 2) Measure 40 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 120 mL of 37% hydrochloric acid solution, slowly pour it into the beaker containing the hydrogen peroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0081] 3) The cut carbon nanotube film is placed in an oxidizing solution to allow the carbon nanotube film to self-expand at room temperature; the expansion time is about four minutes and the height reaches 18 mm.
[0082] 4) Take out the expanded sample and place it in a beaker filled with water, add 2 mol / L sodium hydroxide solution to neutralize until the pH is 7, and rinse with deionized water again to remove impurities;
[0083] 5) Finally, the sample was placed in a freeze dryer and freeze-dried at -56°C for 18 hours to obtain a three-dimensional layered porous carbon nanotube foam.
[0084] Example 7
[0085] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0086] 1) Cutting the carbon nanotube film into film slices of 50 mm × 30 mm × 0.2 mm;
[0087] 2) Measure 80 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 40 mL of 37% hydrochloric acid solution and slowly pour it into the beaker containing sodium hydroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0088] 3) The cut carbon nanotube film is placed in an oxidizing solution to allow the carbon nanotube film to self-expand at room temperature; the expansion time is about four minutes, and the expansion height reaches 32 mm.
[0089] 4) Take out the expanded sample and place it in a beaker filled with water, add a 2 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it again with deionized water to remove impurities;
[0090] 5) Finally, the sample was placed in a vacuum oven and dried at 150° C. for 1 hour to obtain a three-dimensional layered porous carbon nanotube foam.
[0091] The actual pictures of the carbon nanotube film and carbon nanotube foam of this embodiment are as follows: Figure 6 shown.
[0092] Example 7
[0093] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0094] 1) Cutting the carbon nanotube film into film slices of 50 mm × 30 mm × 0.2 mm;
[0095] 2) Measure 120 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 40 mL of 37% hydrochloric acid solution and slowly pour it into the beaker containing sodium hydroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0096] 3) The cut carbon nanotube film is placed in an oxidizing solution to allow the carbon nanotube film to self-expand at room temperature; the expansion time is about four minutes, and the expansion height is about 12 mm.
[0097] 4) Take out the expanded sample and place it in a beaker filled with water, add a 2 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it again with deionized water to remove impurities;
[0098] 5) Finally, the sample was placed in a freeze dryer and freeze-dried at -56°C for 18 hours to obtain a three-dimensional layered porous carbon nanotube foam.
[0099] Example 8
[0100] A method for preparing a three-dimensional layered porous carbon nanotube foam, the specific steps are as follows:
[0101] 1) Cutting the carbon nanotube film into film slices of 50 mm × 30 mm × 0.2 mm;
[0102] 2) Measure 40 mL of 30% hydrogen peroxide solution and place it in a beaker, measure 40 mL of 37% hydrochloric acid solution and slowly pour it into the beaker containing sodium hydroxide solution along a glass rod, stir evenly, and obtain an oxidizing solution;
[0103] 3) The cut carbon nanotube film is placed in an oxidizing solution, and the solution is heated during the expansion process, and the temperature is maintained at 60° C. The expansion takes about two minutes and the height reaches 40 mm.
[0104] 4) Take out the expanded sample and place it in a beaker filled with water, add a 2 mol / L sodium hydroxide solution to neutralize it until the pH is 7, and rinse it again with deionized water to remove impurities;
[0105] 5) Finally, the sample was placed in a freeze dryer and freeze-dried at -56°C for 18 hours to obtain a three-dimensional layered porous carbon nanotube foam.
[0106] The scanning electron microscope images of the carbon nanotube foam in this example at different magnifications are as follows: Figure 7 shown.
[0107] Experimental Results
[0108] 1. Preparation process of three-dimensional hierarchical porous carbon nanotube foam Figure 1 As shown, a mixed solution of hydrochloric acid and hydrogen peroxide is used as an oxidizing solution, and the two react to produce a large number of bubbles. Under the action of the bubbles, the carbon nanotube film is peeled off and layered in the solution, spontaneously expands, and the thickness increases. After neutralization with an alkaline solution, rinsing with deionized water, and drying, an ultra-light three-dimensional layered porous carbon nanotube foam with controllable shape, structure, and density is finally obtained.
[0109] 2. The thickness of the carbon nanotube film of Example 1 changes with the reaction time. Figure 3 As shown, the ultra-thin carbon nanotube film (0.2 mm) expands rapidly after being immersed in the solution for about one minute, and its thickness reaches about 2.5 mm. After being immersed in the solution for three minutes, a typical hierarchical porous structure appears, and its thickness reaches 16 mm.
[0110] 3. Comparison of the carbon nanotube foam phase prepared in Example 1 with the original carbon nanotube film in terms of density, thickness, volume, width and length. Figure 4 As shown, compared with the latter, the former has a density reduced by 97%, a thickness increased by 7900%, a volume increased by 3172%, and a width and length reduced by 25% and 27% respectively.
[0111] 3. The carbon nanotube foam sample prepared in Example 4 is as follows Figure 5 As shown in Figure 2, about 4 minutes after the carbon nanotube film was placed in the solution, the thickness of the carbon nanotube film increased rapidly to 9 cm, and the carbon nanotube foam appeared as shown in Figure 2. Figure 5 The three-dimensional layered structure shown.
[0112] 4. Carbon nanotube foam samples prepared in other embodiments are as follows Figure 8 As shown, the shapes of carbon nanotube foams are cuboid (width greater than length), cuboid with a hole in the middle, cuboid (length greater than width), cylinder, and irregular body. It can be seen that after designing the pattern of the carbon nanotube film, shape-controllable carbon nanotube foam can be prepared.
[0113] The present invention provides an efficient preparation method of three-dimensional carbon nanotube foam with controllable density, structure and shape. Hydrochloric acid and hydrogen peroxide are used as oxidizing solutions for self-expansion of carbon nanotube film. At room temperature, the thickness of 9 cm can be reached in only about four minutes. In the process, the pattern of the carbon nanotube film can also be designed to prepare carbon nanotube foam with controllable shape.
[0114] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a three-dimensional hierarchical porous carbon nanotube foam, characterized in that: The specific steps are as follows: (1) shearing the carbon nanotube film; (2) stirring the hydrogen peroxide solution and the hydrochloric acid solution to obtain an oxidation solution; (3) placing the carbon nanotube film cut in step 1) in the oxidizing solution in step 2) to perform a self-expansion process of the carbon nanotube film; (4) taking out the sample obtained in step 3), placing it in water, adding an alkaline solution to neutralize it until the pH is 7, and washing it with water to remove impurities; (5) Drying the sample obtained in step 4) to remove moisture, thereby obtaining a three-dimensional hierarchical porous carbon nanotube foam; The self-expansion time in step (3) is 2 to 4 minutes; The self-expansion height in step (3) is 12 mm to 9 cm; The self-expansion process in step (3) is carried out at room temperature or at 50°C to 70°C; The volume ratio of the hydrogen peroxide solution to the hydrochloric acid solution in step (2) is 1-3:1-3; The drying method in step (5) is any one of the following: room temperature drying, vacuum drying, and freeze-drying; The room temperature drying is drying at 25°C for 24 hours; the vacuum drying is drying at 120°C for 1 hour; the freeze-drying is freeze-drying at -56°C for 18 hours; The concentration of the hydrogen peroxide solution in step (2) is 30 wt %, and the concentration of the hydrochloric acid solution is 37 wt %.
2. The preparation method according to claim 1, characterized in that: The alkaline solution in step (4) is a sodium hydroxide solution with a concentration of 0.5 mol / L to 4 mol / L.
Citation Information
Patent Citations
Carbon nanotube sponge and method for making the same
US9102537B2
Carbon nanotube sponge body and preparation method thereof
CN104418316A